Theoretical Description Of A Motion Of A Spherical Bubble In Neighbourhood Of A Falling Particle - P. Basarova (International Mineral Processing Congress, 2012)
The attachment of bubbles onto a collecting surface is an ubiquitous natural phenomenon, playing a critical role in numerous practical processes. The goal of the project is to broaden the knowledge about hydrodynamic interactions between small bubbles and large solids that occur in nature and industrial processes. Focusing on collision processes between a single rising bubble (Db<1 mm) and a larger falling spherical particle in stagnant liquid, the theoretical model describing the bubble trajectory is given here. The model is based on analysis of forces acting on the bubble, and utilizes equation for the bubble motion. Mobile and immobile type of bubble surface mobility are considered. The calculated results are compared with the experimental data; here a high-speed video camera was used to capture the bubble motion and bubble-particle interaction. Very good agreement between experimental and calculated data was found. For both types of surface mobilities, the bubble deviation in the horizontal direction is nearly linear. The proportion constant is bigger for immobile bubble surface and increases with the bubble size. Furthermore, particular forces acting on bubble were studied. A similar course of relative bubble velocity and force impact was observed for identical bubble position. For cases when the bubble centre is close to the particle axis, only deflection in one direction is observed. When the bubble is reaching the maximum trajectory, the force ratio is changed. The bubble is firstly pushed away from the particle, but when it is within close distance from the particle, the bubble is pushed towards the particle.